2013
DOI: 10.4049/jimmunol.1202923
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Heterotypic to Homotypic PDK1 Homodimerization Is Essential for TCR-Mediated NF-κB Activation

Abstract: Strong NF-κB activation requires ligation of both the CD28 co-receptor and TCR. PDK1 acts as a scaffold by binding both PKCθ and CARMA1 and is therefore essential for signaling to NF-κB. Here, we demonstrate the importance of PDK1 threonine (Thr)-513 phosphorylation in regulating the intermolecular organization of PDK1 homodimers. Thr-513 is directly involved in heterotypic PDK1 homodimer formation, in which binding is mediated through the pleckstrin homology (PH) and kinase domains. Upon activation, phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
(39 reference statements)
2
15
0
Order By: Relevance
“…Recent studies show that phosphorylation of the PDK-1 PH domain by TCR/CD28 signaling induces formation of PDK-1 dimers able to bind and phosphorylate its substrates, PKCθ and AKT. 46 We found that DGKζ limits DAG-dependent PDK-1 activation by stabilizing PKCθ, which complements this model and helps to clarify the close interrelation of these kinases. PKCθ interacts physically and functionally with AKT to activate the NFκB pathway, 47 which correlates with enhanced NFκB activation and PDK-1-dependent AKT phosphorylation in DGKζ-null T cells.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Recent studies show that phosphorylation of the PDK-1 PH domain by TCR/CD28 signaling induces formation of PDK-1 dimers able to bind and phosphorylate its substrates, PKCθ and AKT. 46 We found that DGKζ limits DAG-dependent PDK-1 activation by stabilizing PKCθ, which complements this model and helps to clarify the close interrelation of these kinases. PKCθ interacts physically and functionally with AKT to activate the NFκB pathway, 47 which correlates with enhanced NFκB activation and PDK-1-dependent AKT phosphorylation in DGKζ-null T cells.…”
Section: Discussionsupporting
confidence: 75%
“…Recent studies show that phosphorylation of the PDK‐1 PH domain by TCR/CD28 signaling induces formation of PDK‐1 dimers able to bind and phosphorylate its substrates, PKCθ and AKT 46 . We found that DGKζ limits DAG‐dependent PDK‐1 activation by stabilizing PKCθ, which complements this model and helps to clarify the close interrelation of these kinases.…”
Section: Discussionsupporting
confidence: 75%
“…They showed that a basal homodimer population (of ∼20 %) existed mainly in the cytoplasm of resting cells that was increased (to 40 %) upon growth factor stimulation. Even though the destabilization of the PDK1 inhibitory homodimer upon translocation and autophosphorylation would be expected to trigger an active monomeric form of PDK1, a recent article by Kang et al [19] suggested that the phosphorylation of Thr 513 would probably trigger the formation of a different PDK1 homodimer conformer (possible 'active' homodimer) [19]. Moreover, they determined that the presence of a complete PH domain was strictly necessary for the maintenance of PDK1 homodimers at steady state, but did not require a functional lipid-binding domain [18].…”
Section: Conformational Regulations Of Pdk1 and Homodimerizationmentioning
confidence: 99%
“…1 the plasma membrane by binding to PtdIns(3,4,5)P 3 via their respective PH domains [2][3][4] and involves the formation of a PKB-PDK1 heterodimer complex [5]. This consists of phosphorylation events [13,14], subcellular localization [15,16] and conformational rearrangements including PDK1 homodimerization [17][18][19]. Owing to the profuse number of signalling pathways controlled by PDK1 that are involved in cancer [7] and other diseases, great efforts have been dedicated to understanding how PDK1 itself is regulated and how it in turn regulates its different substrates spatially and temporally.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, PtdIns(3,4,5)P 3 binding to PDK1 in live cells was shown to elicit the formation of PDK1 homodimers [13, 19] and to trigger the autophosphorylation of the PDK1 PH domain residue 513. This, was suggested to be due to the disruption of an autoinhibitory PDK1 homodimer conformer [13, 21, 22]. This mechanism still remains to be defined.…”
Section: Introductionmentioning
confidence: 99%